Analysis of Time for Providing Outpatient Medical Record Documents for General Old Patients at the Gondang Community Health Center, Tulungagung Regency - Saputri, Dita Oisina Gusti; Wardani, Ratna (Universitas STRADA Indonesia, 2022)
The time to provide medical record documents quickly and accurately is one of the factors that can influence the quality of health services. The sooner the provision of medical record documents is found, the faster the service will be provided to the patient. The focus of this research is to determine the time needed to provide outpatient medical record documents for general old patients at the Gondang Tulungagung Community Health Center. This research uses a qualitative research method with a case study approach which aims to examine and establish validity by analyzing from various perspectives. The informants in this research were 3 people, namely the staff of the Community Health Center and 1 triangulator, namely the Head of the Gondang Community Health Center. The results of this research show that: the policy for providing medical records carried out by medical records officers has been implemented well in accordance with existing regulatory standards, standard operational procedures regarding the flow of providing medical record documents at the Gondang Community Health Center, Tulungagung Regency have been implemented well based on the SOP set by the head community health centers and the Ministry of Health, the time for providing outpatient medical record documents for general old patients at the Gondang Health Center, Tulungagung Regency has a time range between 2-5 minutes and less than 10 minutes, and the factors causing delays in the time for providing outpatient medical record documents for general old patients are in Gondang Community Health Center, Tulungagung Regency, where medical record documents were lost. It is hoped that medical record officers can maintain good service to patients and will be even more effective if the service provided can be improved by minimizing patient waiting time and providing friendlier service.